2010
DOI: 10.1161/circep.109.929240
|View full text |Cite
|
Sign up to set email alerts
|

A ZASP Missense Mutation, S196L, Leads to Cytoskeletal and Electrical Abnormalities in a Mouse Model of Cardiomyopathy

Abstract: Background-Dilated cardiomyopathy (DCM) is a primary disease of the heart muscle associated with sudden cardiac death secondary to ventricular tachyarrhythmias and asystole. However, the molecular pathways linking DCM to arrhythmias and sudden cardiac death are unknown. We previously identified a S196L mutation in exon 4 of LBD3-encoded ZASP in a family with DCM and sudden cardiac death. These findings led us to hypothesize that this mutation may precipitate both cytoskeletal and conduction abnormalities in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…Recently, it was reported that a Z-disc protein, ZASP, formed a macromolecular complex with hNav1.5, but there was no direct interaction between ZASP and hNav1.5, and a ZASP mutation disturbed the hNav1.5 function without affecting the localization of hNav1.5. 37 The function of hNav1.5 in cardiomyocytes may be regulated by a fine-tuning mechanism in which many proteins are directly or indirectly involved. Finally, although the loss of hNav1.5 function is often associated with prolongation of PR and QRS, no conduction delay was observed in ECGs from both patients carrying the SLMAP mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that a Z-disc protein, ZASP, formed a macromolecular complex with hNav1.5, but there was no direct interaction between ZASP and hNav1.5, and a ZASP mutation disturbed the hNav1.5 function without affecting the localization of hNav1.5. 37 The function of hNav1.5 in cardiomyocytes may be regulated by a fine-tuning mechanism in which many proteins are directly or indirectly involved. Finally, although the loss of hNav1.5 function is often associated with prolongation of PR and QRS, no conduction delay was observed in ECGs from both patients carrying the SLMAP mutations.…”
Section: Discussionmentioning
confidence: 99%
“…In some previous studies focusing on the establishment of genetically modified mice associated with LVNC candidate genes, 9,[20][21][22][23] the notch signaling pathway has been found to play a vital role in the development of LVNC. Cardiac-specific inactive Mib1 (an E3 ubiquitin ligase of NOTCH ligands) in mice could cause LVNC by disrupting the Notch pathway.…”
Section: N49smentioning
confidence: 99%
“…5) Nevertheless, neither cardiac-specific Cypher knockout mice nor the transgenic mice with cardiacspecific expression of the ZASP-p.S196L mutation showed the expected phenotype of LVNC. 22,23) Therefore, only various parts of mouse models can effectively reproduce the LVNC phenotype. These results suggest that the different genetic background between mice and humans may affect the development of LVNC.…”
Section: N49smentioning
confidence: 99%
“…This work represents a novel framework to understand the development of conduction defects and arrhythmias in subjects with cardiomyopathies, including DCM. 30 …”
Section: A Zasp Missense Mutation S196l Leads To Cytoskeletal and Ementioning
confidence: 99%